A New Insight into Corn Yield:Trends from 1987 through 2015. Issue 5 (30th June 2017) - Assefa, Yared; Prasad, P. V. Vara; Carter, Paul; Hinds, Mark; Bhalla, Gaurav; Schon, Ryan; Jeschke, Mark; Paszkiewicz, Steve; Ciampitti, Ignacio A.
Abstract : Average corn ( Zea mays L.) yields have significantly increased in the past decades. However, it is not clear whether this average corn yield gain is primarily due to yield improvement at all yield environments, to a decrease in the proportion of low‐yielding (LY) environments, or to both. The objectives of this analysis were to examine yield trends across different physical and yield environments, to review possible genetic, environmental, management, and interaction (G × E × M) factors that contributed to yield changes, and to suggest direction for future research. Corn hybrid‐by‐seeding rate trials were conducted from 1987 to 2015 across North America. The experimental design for the trials was a randomized complete block design with a split‐plot arrangement. Synthesis analysis using hierarchical modeling was applied on these meta‐data (181, 395 data points). Primary outcomes from this synthesis analysis were: (i) a comparable increase in average corn yield across latitudes, (i.e., with rates of 108, 97, and 117 kg ha −1 yr −1 for the 35 to 40°, 40 to 45°, and 45 to 50° N latitude groups, respectively), (ii) when yield changes were evaluated by yield environment, improvement was recorded in the high‐ (HY) and very high‐yielding (VHY) environments at the average maximum rate of 50 kg ha −1 yr −1, (iii) the proportion of HY and VHY environments increased by 50% in the years 2007 to 2015 compared with 1987 to 1996, (iv) yield for medium‐yielding (MY) and LY environments did not significantly change over time, and (v) the proportion of LY and MY environments has decreased over time. In summary, increases in the yield ceiling and proportion of HY environments were the main reasons for yield improvement. Future research might continue to focus on yield improvement and further shrinking of LY and MY environments via improved hybrid and crop management technologies.